Pengaruh Budaya Organisasi, Motivasi Kerja dan Disiplin Kerja terhadap Komitmen Organisasi Pada PT. Charoen Pokphand Indonesia Food Medan - JHONI TARULI TUA BUTAR-BUTAR; Sunaryo Sunaryo (Universitas Harapan Medan, 2023)
This study aims to determine the effect of organizational culture, work motivation, and work discipline on organizational commitment at PT. Charoen Pokphand Indonesia Food Medan. This study uses an associative method with a quantitative approach. In this study, the entire population became the sample, namely 89 employees at PT. Charoen Pokphand Indonesia Food Medan. The data collection technique used in this study was a questionnaire. The data analysis technique used multiple linear regression, normality test, multicollinearity test, and heteroscedasticity test. The results showed that organizational culture has a significant effect on organizational commitment, work motivation has a significant effect on employee organizational commitment, work discipline has a significant effect on organizational commitment, and organizational culture, work motivation, and work discipline have a significant effect on organizational commitment.